1997
DOI: 10.1016/s0014-5793(97)01271-4
|View full text |Cite
|
Sign up to set email alerts
|

Design of μ selective opioid dipeptide antagonists

Abstract: We have recently designed potent delta selective opioid antagonist dipeptides on the basis of a simple conformational analysis. Following a similar procedure we found a mu selective dipeptide antagonist, 2,6-dimethyl-Tyr-D-Phe-NH2. Although its selectivity is not as high as those of the quoted delta selective dipeptides it has good in vitro activity and looks very promising for further development since the 2,6-dimethyl-Tyr-D-Phe message, like the delta selective 2,6-dimethyl-Tyr-1,2,3,4-tetrahydroisoquinoline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 30 publications
1
25
1
Order By: Relevance
“…In addition, the presence of the secondary amino group into the six-membered isoquinoline rings in the L-and D-Htc residues (peptides B and C of Figure 1) will often results in cis-trans isomerism of the Xxx-Htc bond. 12 In a benzazepine structure, such as present in the Hba-Gly mimetic, both trans and gauche (ϩ) conformers ( 1 ϭ 180°and ϩ60°) are accessible. 9 This FIGURE 1 Primary structure of the synthetic PTK substrates.…”
Section: Peptide Design and Synthesismentioning
confidence: 99%
“…In addition, the presence of the secondary amino group into the six-membered isoquinoline rings in the L-and D-Htc residues (peptides B and C of Figure 1) will often results in cis-trans isomerism of the Xxx-Htc bond. 12 In a benzazepine structure, such as present in the Hba-Gly mimetic, both trans and gauche (ϩ) conformers ( 1 ϭ 180°and ϩ60°) are accessible. 9 This FIGURE 1 Primary structure of the synthetic PTK substrates.…”
Section: Peptide Design and Synthesismentioning
confidence: 99%
“…In the brain, µ-opioid receptors (MORs) can interfere with the control of food intake via their role in the ‘reward' system [37]. Previous studies showed that various proteolytic moieties released from ingested protein exhibit µ-opioid activity in vitro [38,39,40,41]. Also, peptides derived from the digestion of protein could be delivered into the portal blood after crossing the enterocyte mucosa [42].…”
Section: Induction Of Intestinal Gluconeogenesis and Protein-induced mentioning
confidence: 99%
“…2 Due to the unique biological properties of the Dmt-Tic motif, intensive structure-activity studies were conducted in order to develop bifunctional or heterofunctional opioid ligands. 3 The extensive modifications included N-alkylation, 4 change of the position of hydroxyl and methyl groups on the tyramine ring, 5 introduction of a b-methyl to the Dmt residue, 6 modification of the 5-7 positions of Tic aromatic ring with various groups, such hydroxyl, halogen, nitro, and phenyl, 7 as well as substitution of Tic with its D D-isomer, D D-or L L-Phe, 8 heteroaromatic or heteroaliphatic nuclei, 9 the conversion of the Cterminal carboxyl group to amide, 1,4b ester, 4b and alcohol, 1,10 and conjugation of a third aromatic center at the C-terminal with or without interposing linkers. 4c,11 Many of the analogues exhibited the desired properties, including enhanced d-opioid antagonism, 1-11 conversion from a d antagonist to a d agonist, 11a the appearance of opioids with mixed l agonist/d antagonist properties, 4b,c,11a,b and the development of an irreversible fluorescent d antagonist.…”
mentioning
confidence: 99%
“…19 The combination of Dmt with Tic, on the other hand, greatly enhanced the interaction with d-opioid receptors. 1 Furthermore, substitution of Dmt (7) by Tic (8) or Phe (9) revealed a weaker l-opioid receptor affinity than 7 demonstrating the efficacy of Dmt in the interaction with opioid receptor binding sites. Although Phe was observed to enhance the interaction with l-opioid receptors, 4c,8 Tic and Phe had similar K i values to that of the homodimer, 12 substantiating earlier studies that Tic has a preference for d-opioid receptors.…”
mentioning
confidence: 99%
See 1 more Smart Citation